PERTANGGUNGJAWABAN PIDANA TERHADAP KORPORASI YANG MELAKUKAN TINDAK PIDANA LINGKUNGAN HIDUP - Siregar, Rian Angga Dinata; ', Firdaus; ', Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Corporate crime or White collar crime especially in environmental crime has its ownconstraints. Determining which board is responsible is quite difficult considering the complex formof management in a corporation. Therefore, there are doubts about the possibility of thecorporation to be liable for criminal responsibility and convicted. There are a number of views onthe criminal construction of a corporation so that it has implications for the difficulty ofdetermining corporate wrongdoing for criminal liability. The desire to ensnare corporationsinvolved in environmental crime cases is indeed not easy to realize. Although there is awarenessabout the importance of protecting the environment among law enforcement officials, the fact isthat it is not easy to ensnare perpetrators. Moreover, the majority of environmental criminaldefendants who were brought to court were either free or only sentenced to probation because ofthe difficulty of proving a mistake by a corporation.This research which is entitled "Criminal Accountability Against Corporations ThatConduct Environmental Crimes" aims to find out the effect of errors in determining criminalliability in environmental crime and describe the ideal model of corporate criminal responsibilityfor environmental crime.This research is a normative research or library research. In this case, the author choosesresearch on the principles of law, namely the principle of error in corporations. The data used inthis study is secondary data. The data is then analyzed descriptively qualitative. The theoreticalbasis used are identification theory, substitute accountability theory, and functional perpetratortheory.The result of this research shows that corporate errors can be taken based on intentionsor omissions found in the people who become their tools. These errors are not individual, because itis related to the corporate that is collective. Thus, the corporation has errors that is taken from themanagement or the board of directors in carrying out the duties of their absolute functionary. It ishoped that the uniformity of rules for corporations is made as a subject of criminal law so as toprovide certainty regarding criminal rules and consistency and a strong foundation in imposingcriminal liability on corporation.